Conversational Speech Transcription Using Context-Dependent Deep Neural Networks - Seide, Frank; Li, Gang; Yu, Dong (Interspeech 2011, 2011)
We apply the recently proposed Context-Dependent Deep- Neural-Network HMMs, or CD-DNN-HMMs, to speech-to-text transcription. For single-pass speaker-independent recognition on the RT03S Fisher portion of phone-call transcription benchmark (Switchboard), the word-error rate is reduced from 27.4%, obtained by discriminatively trained Gaussian-mixture HMMs, to 18.5%?aa 33% relative improvement. CD-DNN-HMMs combine classic artificial-neural-network HMMs with traditional tied-state triphones and deep-beliefnetwork pre-training. They had previously been shown to reduce errors by 16% relatively when trained on tens of hours of data using hundreds of tied states. This paper takes CD-DNNHMMs further and applies them to transcription using over 300 hours of training data, over 9000 tied states, and up to 9 hidden layers, and demonstrates how sparseness can be exploited. On four less well-matched transcription tasks, we observe relative error reductions of 22¨C28%.